Optimalisasi Pelafalan Nada Bahasa Mandarin pada Siswa SD YBPK Ngaglik melalui Teknik Drill dan Permainan - Anggrah Diah Airlinda; Dhatu Sitaresmi; Yohanna Nirmalasari (Civiliza Publishing, 2026)
Accurate training in Mandarin language’s tones from an early stage is essential for first and second-grade elementary school students. Through optimizing effective tone pronunciation practice using the drill technique combined with enjoyable game-based activities, students are expected to develop a strong foundation for their subsequent Mandarin language learning. This community service program aimed to improve the ability of students at SD YBPK Ngaglik to pronounce Mandarin tones accurately. The program consisted of three main activities: an introduction to the four Mandarin language tones followed by tone drills using Chinese tongue twisters (raokouling), individual games, and group games. The pre-test and post-test results demonstrated improvements across all assessment aspects. The average score for tone difference increased from 64,5 to 87,8. The average score for accurate tone production improved from 61,8 to 85,6. The average score for clear tone pronunciation increased from 68,2 to 89,1, while the average score for rapid tone production improved from 66,0 to 84,2. This activity successfully resulted in a positive impact by enhancing students' ability to differentiate and correctly pronounce the four tones of Mandarin language.